Environmental, social and governance, intellectual capital and financial performance : evidence from chinese manufacturing companies - Chunya, Ren (2024)
Growing ecological and social problems have prompted companies to pay more attention to environmental, social and governance (ESG) activities as stakeholder theory underscores the importance of stakeholder benefits. Research on the relationship between ESG and financial performance, which may be influenced by intellectual capital (IC), has not been conclusive, with most studies focusing on a single linear relationship and producing mixed results. However, only a few studies have explored the non-linear relationship between ESG and financial performance based on production theory speculations. According to resource-based theory (RBT), the importance of IC in intellectually intensive companies may impact the ESG–financial performance relationship, but related empirical studies are also scarce. To fill these gaps, this study aims to (1) examine whether ESG significantly influences financial performance in a linear and non-linear manner by dividing ESG to ESG managerial practice (ESGM) and ESG controversy control (ESGC) and dividing ESGM to the environmental (E), social (S) and governance (G) pillars; (2) investigate whether IC significantly influences financial performance in a linear and non-linear manner; and (3) detect whether IC significantly moderates the linear and non-linear relationship between ESG and financial performance. To achieve these aims, this study applies fix effect panel regression using secondary data from 2956 Chinese manufacturing companies from years 2018 to 2021. This study also performs a robustness check using the two-stage least squares method and replacing the financial performance indicators. Results show that (1) ESG and ESGM have significant linear and non-linear relationships with financial performance; (2) ESGC only shows a significant linear relationship with financial performance; (3) E, G and IC have significant linear and non-linear relationships with financial performance; (4) S has no relationship with financial performance; (5) IC significantly moderates the linear and non-linear relationships of ESG, ESGM, ESGC and E with financial performance; and (6) IC significantly moderates the linear relationship of S and the non-linear relationship of G with financial performance. This study enriches the empirical application of stakeholder theory, RBT and production theory and combines these theories to fill the gaps in the literature. Another novelty of this study lies in its discussion of non-linear relationships and its combination of non-financial indicators ESG and IC to influence financial performance. By revealing the influence of ESG and IC on financial performance, this study offers a decision-making reference for stakeholders, such as company managers, policymakers and investors. This study provides guidance for the application of ESG and IC in Chinese manufacturing companies.